PENGEMBANGAN BAHAN AJAR TEKS FABEL BERBASIS APLIKASI VIDEO SHOW PADA SISWA KELAS VII SMP HARAPAN BANGSA TANJUNG MORAWA - Yolanda Rara Novandes; Mohammad Joharis Lubis (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
This research aims to describe the effect of problem-based learning strategy assisted by visual media on the ability to write persuasive texts among students in class VIII of SMP Negeri 1 Galang. iThe subjects of this research were 24 students of class VIII-5 (control class) and 28 students of class VIII-7 (experimental class) of SMP Negeri 1 Galang, which were determined by cluster random sampling. The method used in this research is the experimental method with the Posttest-Only Control design. The instrument used in this research is the test (posttest). From the data analysis, it was obtained that the mean value of the posttest in the control class was 62 and the standard deviation was 7.59, while the mean value of the posttest in the experimental class was 88.64 and the standard deviation was 6.18. Before conducting the hypothesis test, the analysis requirements were tested, namely the normality test and the homogeneity test. Based on the results of data analysis, it was found that the data of the posttest of the control class and the experimental class were normally distributed and homogeneous. iConsulted itcount with ittable at the significance level of 0.05 with dk=n1 + n2 -2 = 28 + 24 - 2= 50 obtained ttable = 1.675905. Because tcounti> ttabel 13.95 > 1.68, so this hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. The result of the hypothesis test shows that the problem-based learning strategy assisted by visual media has a positive influence on the ability to write persuasive texts among students in class VIII of SMP Negeri 1 Galang.